Current understanding of photophobia, visual networks and headaches. (November 2019) - Noseda, Rodrigo; Copenhagen, David; Burstein, Rami
Objective: To review clinical and pre-clinical evidence supporting the role of visual pathways, from the eye to the cortex, in the development of photophobia in headache disorders. Background: Photophobia is a poorly understood light-induced phenomenon that emerges in a variety of neurological and ophthalmological conditions. Over the years, multiple mechanisms have been proposed to explain its causes; however, scarce research and lack of systematic assessment of photophobia in patients has made the search for answers quite challenging. In the field of headaches, significant progress has been made recently on how specific visual networks contribute to photophobia features such as light-induced intensification of headache, increased perception of brightness and visual discomfort, which are frequently experienced by migraineurs. Such progress improved our understanding of the phenomenon and points to abnormal processing of light by both cone/rod-mediated image-forming and melanopsin-mediated non-image-forming visual pathways, and the consequential transfer of photic signals to multiple brain regions involved in sensory, autonomic and emotional regulation. Conclusion: Photophobia phenotype is diverse, and the relative contribution of visual, trigeminal and autonomic systems may depend on the disease it emerges from. In migraine, photophobia could result from photic activation of retina-driven pathways involved in the regulation of homeostasis, making its association with headache more complex than previously thought.